Laparoscopic surgical robotics (1999–2023): a bibliometric exploration of technological evolution and research frontiers - Cao, Peng; Wang, Guohui; Ling, Hao; Zeng, Yijia; Yi, Bo; Zhu, Shaihong (Journal of robotic surgery, 2025)
Advancements in robotic-assisted laparoscopic surgery have significantly propelled research development. This study employs bibliometric and visualization techniques to examine the current landscape and emerging trends in this field. Utilizing the Web of Science Core Collection, this study extracted publications on robotic-assisted laparoscopic surgery up to 2023 and conducted bibliometric analysis with systematically integrated data visualization tools and analytical algorithms. Analysis of 8375 scholarly works (6838 articles; 1537 reviews) demonstrates a notable surge in academic productivity and citation impact over the 24-year observation period, particularly accelerating after 2019. Yonsei University ranked first in institutional contributions, while the United States retained its dominance in publication output. Surgical Endoscopy topped the publication volume, whereas European Urology excelled in H-index and Impact Factor rankings. Prominent researchers include Kaouk JH and Menon M, the latter of whom attained the highest average citation count. Frequent keywords such as “robotic surgery” and “laparoscopic surgery” indicate the primary focus areas within the field. Robotic-assisted laparoscopic surgery shows great potential, particularly for abdominal tumor procedures. Future research should emphasize global collaboration, improve research quality, and address geographic disparities to unlock new frontiers in precision surgery and enhance patient outcomes globally.